The Butterfly Effect: Creating and Recreating the Story of Madame Butterfly, on Paper and on Stage - Szuster, Magdalena (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The consequences of the partially coerced opening of Japan to the Western world in the second half of the 19th century went far beyond economic and political goals and considerations. The previously secluded land almost instantly became a source of artistic inspiration and endless fascination. Japonisme, the term by which the latest craze become known in France, was no passing fad. For many decades, Western artists, most of whom had never set foot in Japan, derived profound inspiration from all facets of the mysterious culture which unfolded in the period. Thus, with scant information and a lack of accurate records being available, common gossip and unfounded rumor filled in the blanks of official reports and naval tales, connecting the dots between the real and the imagined. In this paper, I succinctly examine the story of Madame Butterfly, cutting across time, genre and borders in the works of John Luther Long, David Belasco, Giacomo Puccini and Claude-Michel Schönberg/Alain Boublil. I contextualize the selected narratives within their socio-political frameworks, but also consider the ramifications of the past and present-day adaptations from the 21st-century perspective, in the light of current struggles for (adequate) representation. Lastly, I examine the production of Miss Saigon (2019–22) at the Music Theatre of Łódź, Poland to compare how the staging of such a musical in a predominantly racially homogenous country affects the perception of Orientalist works. As such this section is a case study based on personal interviews conducted by the author with the producers and cast members.